2000
DOI: 10.1177/009155210002800101
|View full text |Cite
|
Sign up to set email alerts
|

Career Stages of Community College Faculty: A Qualitative Analysis of their Career Paths, Roles, and Development

Abstract: Twenty-two faculty at a Midwestern community college were interviewed to elicit their perceptions of their career paths, their early-stage career roles, and the role played by faculty development in their early careers. Based on the interview data, the majority did not foresee their career path and chose the community college because of its emphasis on teaching. Participants indicated that their career roles changed over time from an emphasis totally on teaching to one that included supplemental activities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…Although the new faculty members interviewed for Twombly's study (2005) considered the community college a legitimate work site that they intentionally sought, they had not foreseen community college teaching as a career goal when they began graduate school. This finding is confirmed by Fugate and Amey (2000) in their study of faculty career stages and by Wolf-Wendel, Ward, and Twombly (2007) in their study of community college faculty mothers with young children. These women, some with Ph.D.s, indicated they intentionally chose to teach in a community college because they thought it would be easier to balance family and work there than in a four-year college or university.…”
Section: Is Community College Teaching a Profession?mentioning
confidence: 64%
See 3 more Smart Citations
“…Although the new faculty members interviewed for Twombly's study (2005) considered the community college a legitimate work site that they intentionally sought, they had not foreseen community college teaching as a career goal when they began graduate school. This finding is confirmed by Fugate and Amey (2000) in their study of faculty career stages and by Wolf-Wendel, Ward, and Twombly (2007) in their study of community college faculty mothers with young children. These women, some with Ph.D.s, indicated they intentionally chose to teach in a community college because they thought it would be easier to balance family and work there than in a four-year college or university.…”
Section: Is Community College Teaching a Profession?mentioning
confidence: 64%
“…Recruiting potential faculty members is an important issue for community colleges because, as Fugate and Amey (2000) argue, some of those who become community college faculty have not always seen teaching there as a desired career goal. In their qualitative single-institution study of faculty members in their few years at the community college, Fugate and Amey (2000) found that faculty who chose to teach at Midwest Community College did so because they did not want to go through the tenure process, which was viewed as a deterrent to teaching in a four-year institution.…”
Section: Recruitmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Continued professional deVelopment was seen as the responsibility of the faculty member and the role of the institution was to provide support. The views ofliberal arts and technical-vocational faculty were similar, as were comparisons by gender and cultural ethnicity (Fugate & Arney, 2000).…”
Section: Burnout In Nursing Educationmentioning
confidence: 78%